Study about Cancer and Potential Death: Updated Role of Mindfulness - Tacon, A. M. (New Horizons in Medicine and Medical Research Vol. 5, 2022)
Patients suffering with chronic progressive diseases like cancer must deal with the reality of loss practically on a daily basis as their condition worsens: as treatments and side effects take their toll; and death is a likely outcome. One intervention that holds promise in the combined area of thanatology (death) and cancer is mindfulness-based stress reduction. The objective here is to provide an update as to mindfulness interventions that focus on death and loss-related factors in those with cancer A plethora of cancer studies indicates its effectiveness in producing beneficial outcomes, for example, reduction in scores for stress, anxiety, etc. While recent research advances the use of mindfulness interventions to include loved ones and caregivers, of those with cancer, future studies of mindfulness interventions also are needed for terminally ill where disease and death, loss and grief intersect.